Effects of dyadic patterns and proficiency pairing on Chinese EFL learners’ second language learning in collaborative writing - Li, Ningning; Liu, Yingliang (Frontiers in Psychology, 2022)
Research on Collaborative Writing (CW) has proliferated over recent decades, but the role that pair dynamics plays in second language (L2) learning remains unclear. This study compared the effect of dyadic interactions and proficiency pairing in CW on L2 learning. Sixty-two Chinese EFL learners participated in this study, forming three types of proficiency pairing, including 12 high-high pairs, 12 high-low pairs, and seven low-low pairs. All dialogs were audio-recorded and analyzed for dyadic patterns, as well as frequency, types, and solutions of Language-Related Episodes (LREs). The findings indicated that lexis-focused LREs took the largest proportion of LREs, followed by discourse-focused LREs and grammar-focused LREs in all groups. However, compared with proficiency pairing, the efficacy of dyadic interactions has a greater impact on L2 learning. Learners displaying collaborative patterns significantly produced more LREs and correctly solved the majority of the conflicts than those in non-collaborative interactions, while neither the total number nor solutions of LREs reached significance in different proficiency pairing groups. Pedagogical implications on implementing CW in L2 writing classrooms are discussed.